2012
DOI: 10.1007/s10787-012-0128-6
|View full text |Cite
|
Sign up to set email alerts
|

Green-lipped mussel (Perna canaliculus) extract efficacy in knee osteoarthritis and improvement in gastrointestinal dysfunction: a pilot study

Abstract: Green-lipped mussel significantly improved knee joint pain, stiffness and mobility. We report for the first time that the administration of GLM extract also significantly improved GI symptoms by 49% in OA patients. Given that GI dysfunction is linked to analgesic medication use, we further conclude that the therapeutic efficacy of the GLM extract used was possibly correlated to its effects on GI function by improving GSRS scores from baseline. Results from this trial highlight the requisite for further clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 24 publications
1
42
0
Order By: Relevance
“…Previously reviewed published human studies of probiotics and of prebiotics (a nutritional supplement favoring the growth and increasing the lifespan of probiotic bacteria) demonstrate their effects on several clinical scenarios (Vitetta and Sali 2008;Vitetta et al 2012Vitetta et al , 2014a. Their beneficial effects can occur when the internal human environment is influenced by the commensal/probiotic environment throughout the digestive tract.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously reviewed published human studies of probiotics and of prebiotics (a nutritional supplement favoring the growth and increasing the lifespan of probiotic bacteria) demonstrate their effects on several clinical scenarios (Vitetta and Sali 2008;Vitetta et al 2012Vitetta et al , 2014a. Their beneficial effects can occur when the internal human environment is influenced by the commensal/probiotic environment throughout the digestive tract.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid and whole extracts reinforce the anti-inflammatory therapeutic activity of acetylsalicylic acid and indomethacin while concomitantly exhibiting gastroprotective activity (Rainsford and Whitehouse 1980). Supportive data indicates that supplementation with whole P. canaliculus extract may support GIT function and even show gastroprotective activity when administered with anti-inflammatory and analgesic medications in patients with OA (Coulson et al 2012(Coulson et al , 2013. Further, preliminary evidence has demonstrated that the SFE lipid-rich fraction significantly reduced colonic damage in an inflammatory bowel disease (IBD) animal model (Tenikoff et al2005) and partially improved selected indicators of intestinal inflammation and intestinal morphology in an animal model of chemotherapy-induced mucositis.…”
Section: Gastroprotective Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Results of as a systematic review suggest that a Perna canaliculus supplement may be superior to placebo in the treatment of mild to moderate osteoarthritis [1], probably linked to an analgesic effect. In addition, Perna canaliculus inhibits the 5-lipoxygenase and cyclo-oxygenase 1 and 2 pathways [2], which lead to the formation of the leukotrienes and prostaglandins that contribute to the inflammatory process [3] [4]. Ribes nigrum leaf, which is particularly rich in polyphenols, is among the most active extracts for inhibiting cytosolic phospholipase A2 alpha [5], and curcumin has been used for a long time in complementary medicine for a series of conditions, including osteoarthritis, because of its anti-inflammatory and anti-oxidant effects [6] [7] [8].…”
Section: Introductionmentioning
confidence: 99%